2020
DOI: 10.3390/min10121125
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Apatite as Genetic Indicators of the Evate Apatite-Magnetite Deposit, NE Mozambique

Abstract: The Evate deposit is a Neoproterozoic (~590 Ma) magnetite-apatite-carbonate body emplaced parallel to foliation of the Monapo granulite complex in NE Mozambique. A complicated history of the deposit is recorded in apatite textures visualized in cathodoluminescence (CL) images. In spite of different solid and fluid inclusions, mineral assemblages, and the CL textures, electron probe microanalyses indicate relatively consistent apatite compositions corresponding to fluorapatite (XF = 0.51–0.73, XOH = 0.21–0.47, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The results of this study open a new path to understanding the mineralogy and chemistry of several rare earth deposits. Naturally formed cerianite has been found: (1) in association with bastnasite/monazite; [31][32][33][34][35][36] (2) as a secondary mineral, as a result of hydrothermally-altered carbonate/apatite weathering; 2,31,37,38 (3) replacing early crystallised ancylite and uorocarbonates; 40 (4) as an overgrowth on Ce-depleted monazite. 40 Our experiments explain these ndings in natural deposits and are consistent with the decarbonation processes of rare earth carbonates due to the crystallisation of Ce-carbonates under low-hydrothermal conditions (35-205 °C).…”
Section: Implications For Natural Systems and Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study open a new path to understanding the mineralogy and chemistry of several rare earth deposits. Naturally formed cerianite has been found: (1) in association with bastnasite/monazite; [31][32][33][34][35][36] (2) as a secondary mineral, as a result of hydrothermally-altered carbonate/apatite weathering; 2,31,37,38 (3) replacing early crystallised ancylite and uorocarbonates; 40 (4) as an overgrowth on Ce-depleted monazite. 40 Our experiments explain these ndings in natural deposits and are consistent with the decarbonation processes of rare earth carbonates due to the crystallisation of Ce-carbonates under low-hydrothermal conditions (35-205 °C).…”
Section: Implications For Natural Systems and Industrymentioning
confidence: 99%
“…[31][32][33][34][35][36] It is identied as a late-stage secondary mineral. 2,31,37,38 For example, A. Mahmoud and Williams-Jones 31 suggested that cerianite is the product of the weathering of minerals containing light REEs such as monazite and bastnasite in their studied granitic batches from Egypt. Similarly, Zaitsev et al 39 found that cerianite formed during the alteration of apatite as a result of carbonate weathering precipitated from groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the usefulness of Ilaps application a range of samples were analysed, such as bulk analysis of archaeological samples, 18,19 imaging of platinum in tumour tissue of a mouse 20 and other biological samples, [21][22][23] geological samples 24,25 or imaging of the corrosion of Ni-based alloy. 26 In addition to Ilaps being used for many transdisciplinary collaborations, it also offers a way to easily handle data from other instruments, such as laser-induced breakdown spectroscopy (LIBS), 27 just by simple conversion of raw data to t the importing format.…”
Section: Introductionmentioning
confidence: 99%